Pengaruh Bioabsorpsi Mangrove Avicennia alba terhadap Limbah Amoniak (NH3) [The Bioabsorbtion Effects of Mangrove Avicennia alba against Ammonia (NH3) ] - Moch. Amin Alamsjah; Mega Puspa Sari; Prayogo Prayogo (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract The pressure on the aquatic environment progressively increasing due to the influx of waste from various activities in areas that have been built in coastal areas. Waste is one of the issues that must be handled properly. Inadequate waste management with the application of inappropriate technology will cause negative effects on the environment because the waste contains harmful chemicals and toxic. One of the common chemicals contained in the waste is ammonia. Utilization of aquatic plants can be used to overcome the problem of ammonia. Mangrove Avicennia alba is a water plant that can be used to absorb ammonia in the water. This research is conducted to determine the effect and the ability of mangrove A. alba as bioabsorption of ammonia in the water. Based on the research conducted, A. alba can act as bioabsorbtion for ammonia in the water. A. alba can absorb ammonia content in water from 10 mg/L to 0 mg/L within seven days with the highest uptakes are in treatment of P3 (5 mg/L) and treatment of P4 (10 mg/L). Treatment of P2 (1 mg/L) is the highest average nitrogen contain with 0.9244 %.